Unraveling meanings of the filipino internet meme a semiotic analysis on internet memes of flood disasters in the Philippines - Machan, Hencille Vera R. (2019)
This study focus on analyzing the meanings behind signs and symbols of internet memes. The researcher integrated the context of flood disasters in the Philippines as basis for the type of the Internet Meme that is studied. Meme studies such as this have little amount of literature, therefore this study is significantly valuable in the growth of the research on Meme topic. Grounded by the Theory of Visual Studies Semiotics, the researcher formulated research questions aimed at analyzing the meanings behind signs and symbols evident in each Internet Meme samples of Philippine flood disasters. The researcher obtained the data samples from Facebook, using the keyword search feature of the website to follow a purposive sampling technique that fits in the context of the study. 36 Internet Meme samples on Philippine flood disasters were retrieved from five keyword searches. Nine themes emerged after analyzing the meanings behind the signs and symbols of each data samples. These nine themes were analyzed with regards to the emerging relationships relating to the context of flood disasters in the Philippines.